PERANCANGAN SYSTEM INFORMASI TOKO SERASIH UNTUK MEMPERMUDAH PELAPORAN PENJUALAN - michael oktavianus; Ibnu Zahran Ramdani; Ardyana Lumban Tobing; Syafta Nuryana (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Bina Sarana Informatika, 2024)
Toko Serasih is a UMKM focused on the management, sales, purchase, promotion, and sale of daily goods. This research aims to develop a web-based information system design to enhance efficiency and solve operational problems. The research method used in the development of the information system for Toko Serasih includes interviews and direct observations of Toko Serasih to determine the system requirements needed for the information system design. The design created in this research encompasses the system development stages using the sequential linear method. The sequential linear method includes system requirements analysis, system design including use cases, database, and interface design, as well as system implementation and testing using black-box testing. The design carried out at Toko Serasih facilitates the seller or store admin in sales reporting, which includes stock management, transaction processes, and financial reporting. In addition, this web-based UMKM provides convenience for buyers in accessing promotions and product information available. The system testing using the black-box testing method shows that all implemented features function well according to user needs. The implementation of the web-based information system at Toko Serasih has proven effective in addressing existing operational performance issues. The designed system not only increases efficiency and accuracy in processing sales reports, including sales, purchases, and promotions at Toko Serasih. Thus, the information system at Toko Serasih is an appropriate solution to improve performance and competitiveness as an UMKM.